Transportation [Technology 2000 analysis and forecast]. - Bretz, E.A.
Future prospects in the field of transportation are outlined by the author in this paper. Topics covered include intelligent transport; fleet operations; smart cars; vehicle safety; in-vehicle data; mass transit; and railways
Keywords: Fleet operations; In-vehicle data; Intelligent transport; Mass transit; Railways; Smart cars; Technology analysis; Technology forecast; Transportation; Vehicle safety